Improved Enhanced Distributed Energy Efficient Clustering (iE-DEEC) Scheme for heterogeneous Wireless Sensor Network - F. Jibreel (MUSURGIA, 2020)
Wireless Sensor Networks (WSNs) contain thousands of sensor nodes which are capable of conveying sensed and captured data from any deployment area to another well –resourced node called the Base station for analysis. Due to the ability of the sensor nodes to relay data from one place to the other, they are found applicable in several areas such as environmental monitoring, military surveillance and home intelligence. The operation of the heterogeneous routing algorithm, E-DEEC (Enhanced Distributed Energy-Efficient Clustering) for heterogeneous networks has been observed carefully. The E-DEEC scheme improved the DEEC algorithm by introducing other nodes called supernodes.